The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1984-70332014v14n3a23
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of induced polyploidy in Dendrobium nobile Lindl. (Orchidaceae)

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 11 publications
2
38
0
2
Order By: Relevance
“…Although previous investigators did not find phenotypic differences in traits among cytotypes in P. spicata (Jones & Larson ), we found that P. spicata plants from tetraploid populations were larger than those from diploid populations. These observations are consistent with findings that polyploid cytotypes are often larger (Vichiato et al ) and more competitive than diploids (Thebault et al ). We also found that all measured traits varied significantly among populations from the same ploidy group, likely in response to local environment and climate (St Clair et al ; Gibson ).…”
Section: Discussionsupporting
confidence: 92%
“…Although previous investigators did not find phenotypic differences in traits among cytotypes in P. spicata (Jones & Larson ), we found that P. spicata plants from tetraploid populations were larger than those from diploid populations. These observations are consistent with findings that polyploid cytotypes are often larger (Vichiato et al ) and more competitive than diploids (Thebault et al ). We also found that all measured traits varied significantly among populations from the same ploidy group, likely in response to local environment and climate (St Clair et al ; Gibson ).…”
Section: Discussionsupporting
confidence: 92%
“…Reduction in corm diameter and corm multiplication rate of treated plants is also one of the negative effects of colchicine treatment which could be the result of polyploidy induction. Decreased diameter of orchid (Dendrobium nobile) pseudobulbs as observed by Vichiato et al (2014) was due to induction of polyploidy and doubling of cell genomic material. It causes increase in utilization of stored food during different growth stages and flowering.…”
Section: Discussionmentioning
confidence: 99%
“…However late flowering in tetraploid orchid (Dendrobium nobile) plants could be associated with increased cell size and cell nuclear volume. As colchicine increases the cell size so these cells need more time and energy for a DNA duplication which reduced the rate of cell division (Vichiato et al, 2014). In brassica plants, (Brassica campestris) there was a delay of 11 days in 50% flowering in colchicine treated plants as compared to control plants (Kumar and Dwivedi, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few studies on breeding orchids due to the long cycle of plants in the Dendrobium genus i. e., which leads to an average flowering development of three to four years (Vichiato et al 2014). Faria et al (2009), Faria et al (2011), and Faria et al (2013, working with Dendrobium crosses, were successful in obtaining three new cultivars (UEL 6, UEL 7 and UEL 8), which expressed the desired characteristics of mother plants such as flower size, flower coloration, flourishing period, number of flowers, plant height, among others.…”
Section: Introductionmentioning
confidence: 99%